Empowering Students' Digital Literacy through Google Classroom: A Case Study of Library-Based Learning in Indonesian School - Isyatur Radhiyah (Indonesian Journal of Education and Social Studies, 2025)
This study aims to explain the implementation of the Digital Literacy Movement through Google Classroom in the school, analyze the challenges faced, and evaluate its impact on students' digital literacy skills. The research subjects included the head librarian, literacy assistant teachers, librarians, and 11th-grade students. The method used was a descriptive qualitative case study. Data collection was conducted through observation, documentation, and interviews, with thematic analysis employing triangulation of sources, techniques, and theories. The study's results indicate that the digital literacy program, implemented through Google Classroom, is effective, with the library serving as both a digital content provider and a learning facilitator. Challenges faced include limited devices, unstable internet connectivity, and student distractions during online learning. Nevertheless, this program successfully increased students' reading interest, critical thinking skills, and collaborative abilities. This research contributes to the development of library-based digital literacy theory and offers a practical model that can be adapted by schools in 3T (frontier, outermost, and disadvantaged) areas. However, this study was limited to a single school context and a short research period, so further research is needed in broader and more diverse contexts.